Galanin neurons in the ventrolateral preoptic area promote sleep and heat loss in mice - Daniel Kroeger (Nature Portfolio, 2018)
Anatomical lesions of the preoptic area (POA) can cause sleep loss while electrical, chemical, or thermal stimulation of POA can induce sleep. To better understand the exact neural function of the POA, this study shows that galanin and GABA+ inhibitory neurons in the ventrolateral POA that project to the wake-promoting tuberomammillary nucleus promote sleep in a stimulation frequency dependent manner.